Performance of porous asphalt incorporating steel fiber - Nur Athirah, Mohd Radzi (2019)
Porous Asphalt (PA) is known as highly permeable asphalt surface that design to be permeable pavements for storm water control and reduce the storm water runoff. However, the structure is subjected to damage from cracking, rutting, stripping and rapid aging under the effects of repeated vehicle loading, hot climates and heavy rainfall. Application of steel fiber benefit in increasing the strength, life period and toughness of road pavement because steel fiber tend to be used to control of crack and strengthen the pavement by resisting tensile cracking. Thus, the aim of this study is to evaluate the performance of these porous asphalt mixtures with the steel fiber and overcome the issue that is related to PA. A mixture contains varying percentages of steel fiber were assessed to check which samples gives the best performance as per the requirement by using laboratory tests which is LA Abrasion, Resilient Modulus, Marshall Stability and Flow and Dynamic creep. The results show that the additions of 0.6% steel fiber give the lowest value of abrasion, while 0.5% fiber content contributes the highest value of Resilient Modulus and Marshall Stability respectively. While 0.3% fiber content is the best for dynamic creep. By ranking method, the optimum fiber content of 0.6% is obtained. PA mixtures modified with steel fiber produce the performance enhancement of PA as a road surfacing material. It is concluded that the asphalt mixtures containing steel fibers could be increases the stability and strength of the mix. For future studies, it is recommended to analyze the effect of various steel fiber length towards porous asphalt performance and an appropriate design procedure for porous asphalt mixture that will render the satisfactory performance of PA during service.